Two Hexapleomera species from Japan, with a new species description and discussion of phylogenetic relationships within Hexapleomera (Crustacea: Tanaidacea) - Tanabe, Yuki; Kakui, Keiichi (Zootaxa, 2019)
We describe Hexapleomera sasuke sp. nov. and provide a supplemental redescription of Hexapleomera urashima Tanabe et al., both of which are based on specimens collected in Japan. Hexapleomera sasuke closely resembles H. urashima, sharing a uropod with four articles, maxillipedal endites with two tiny dorso-subdistal and two distal spiniform setae, a labium with the palp fused to the outer lobe, and the pereopod-1 propodus with an inner subdistal plumose seta. The new species differs from H. urashima in having the basal article of pleopod 3 with three outer plumose setae, the chelipedal carpus with three or four dorsodistal simple setae, the region between the bases of the chelipedal dactylus and fixed finger with three or four simple setae, and deeply pigmented pleopodal rami. We determined partial sequences of the cytochrome c oxidase subunit I (COI) gene (655 nt) from H. sasuke, which proved to be 15.0–15.3% divergent from H. urashima in Kimura 2-parameter (K2P) distance; also in partial sequences of 18S rRNA gene (1888 nt after alignment), 0.8% divergent (K2P distance) was detected between two species. Based on morphology and molecular data, we discuss phylogenetic relationships within Hexapleomera, and propose two morphologically distinct groups, the robusta group and the wombat group.